MINOR CARDIAC ABNORMALITIES IN CHILDREN OF KHARKIV: PECULIARITIES OF .STRUCTURE AND DISTRIBUTION - T. A. Filonova; V. M. Savvo; Yu. V. Sorokolat (Eastern Ukrainian Medical Journal, 2019)
Cardiovascular pathology is one of the urgent problems of modern medicine, including children. The peculiarity of most cardiovascular diseases in children lies in their prolonged formation, tendency to chronic course, less apparent clinical manifestations in the first stages of the disease. Objective. In childhood, large-scale clinical epidemiological studies have not yet become widespread. But the available statistics allows analyzing trends and patterns that reflect the features of cardiovascular pathology in childhood, its role in health of the child population, which was the objective of this paper. Materials and methods. The analysis of medical and statistical documents of 1825 children aged 0–18 years followed up for cardiomyopathies of dysplastic genesis (DGC) in healthcare facilities of Kharkiv. The indications for following up were clinical symptoms and cardiac ultrasound findings during outpatient or inpatient examination in the absence of organic cardiovascular diseases. Results. Most often, clinical manifestation and, accordingly, diagnosis were observed from 4 to 11 years. Most minor cardiac abnormalities persist over the lifetime, and clinical significance may increase with age, contributing to the development of pathology or becoming a risk factor for cardiac pathology. Conclusions. The structure of minor cardiac abnormalities among the children of the dispensary group is heterogeneous: prolapse of the mitral valve (mostly isolated), abnormal chords of the left ventricle and open foramen ovale are most frequently recorded; prolapse of other valves and aneurysms of the atrial septum are very rare. Primary diagnosis of minor cardiac abnormalities mainly takes place at age 4 to 11 years. Summarizing the findings, it can be noted that minor cardiac abnormalities have a relatively high detection rate and constitute a large and heterogeneous dispensary monitoring group.